A mean-variance benchmark for household portfolios over the life cycle - Munk, Claus (Journal of Banking & Finance, 2020)
We embed human capital as an innate, illiquid asset in Markowitz’ one-period mean-variance framework. By solving the Markowitz problem for different values of the ratio of human capital to financial wealth, we emulate life-cycle effects in household portfolio decisions. The portfolio derived with this simple approach matches the optimal portfolio from the much more complicated dynamic life-cycle models. An application illustrates that young households may optimally refrain from stock investments because a house investment combined with a mortgage is more attractive from a pure investment perspective. Another application examines the theoretical support for the observed growth/value tilts in households’ portfolios.